Hall effects on isothermal vertical plate with uniform mass diffusion in the presence of rotating fluid and chemical reaction of first order - Dhananjeya Kumaar, V.S.A.; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution of the combined study of Hall effects on a vertical plate with a rotating fluid in the presence of a homogeneous chemical reaction of first order has been analysed. The dimensionless governing coupled partial differential equations are tackled using the usual Laplace transform technique. The sway of the Hall parameter, Hartmann number, Grashof number, Prandtl number, Schmidt number, chemical reaction parameter on the axial velocity and concentration of the fluid has been depicted graphically.
Keywords: Hall effect; chemical reaction parameter; rotating fluid; angular velocity